THE EFFECTIVENESS OF USING YOUTUBE SHORTS VIDEOS TO ENHANCE SENIOR HIGH SCHOOL STUDENT’S LISTENING ABILITY - Setyawan, Rizky Firman; Supriyono; Aini, Miza Rahmatika; Puspitasari, Hesty (Universitas Islam Balitar, 2024)
Listening is one of the main components in English Comprehension, especial for EFL Learners in Indo006Eesia. However, some EFL learners in senior high school were still struggling with some of the listening methods and media provided by the school such as the bad quality of the audio, incomprehensive accent on the media, and sometimes, the media themselves were unavailable for students to access them. Because of that, the researcher suggested a short-video in a form of YouTube Shorts as a teaching tool for EFL learners in senior high school to help them enhance their listening comprehension. For this research setting, the researcher found the suitable school for the research at SMAN 1 Kademangan Blitar. This research is an experimental research with one-group pretest-posttest design. The quantitative data was the form of data collected in this research. The listening comprehension test was implemented as a form of data collection for this research. A purposeful sampling with consist of 32 tenth grade students from class X-10 at SMAN 1 Kademangan Blitar was the sample used for this research. Several procedures were conducted during this experiment such as administrating a tryout test at SMAN 1 Srengat Blitar, followed by a pretest, giving out the treatment, and providing a posttest exam at SMAN 1 Kademangan Blitar. The results of the experiments would then be measured and analyzed using SPSS 26 to measure the effectiveness of the treatment. The data analysis showed several results in different versions. Firstly, an improvement in mean value from 72.67 at pretest to 88.39 at posttest showed the first step of enhancement. Afterwards, the data were then calculated and analyzed by measuring it’s paired sample t-test and by indicating the significance of Tvalue and Ttable, the result of the analyzation showed that the Tvalue (10.524) was greater than Ttable (2.052). And finally, the significance of the experiment were smaller than the two-tailed significance (0.00 < 0.5). With the following results above, it was proven that the Null Hypothesis was rejected and the Alternative Hypothesis was accepted, meaning that there are significant improvement on senior high school’s listening ability. Making YouTube Shorts Video as an assessment tool effective to use in everyday learning.